Sposoby povyšenija koordinacionnych sposobnostej futbolistov 14-15 let na etape nacal'noj specializacii - Fateh, Z.; Gillard, M. V.; Koutchouk, S. M.; Benzidane, H. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Study the level of development and coordination abilities in young men, age 14-15 years, engage in various complex football programs that will help to develop a technique of their perfections. The importance of coordination of movements and spatial orientation in activity of modern football players constantly increases. It is connected with need to work in the conditions of rigid single combat, in unusual situations, at deficiency of time and space. It is proven that, the use of techniques in a training program contributes to the harmonious development of coordination abilities of the players at the basic stage of specialization.